Dealing with a Latent Danger: Parents Communicating with Their Children about Smoking - Sandra P. Small; Kaysi Eastlick Kushner; Anne Neufeld (Nursing Research and Practice)
The purpose of this study was to understand parental approach to the topic of smoking with school-age preadolescent children. In-depth interviews were conducted with 38 parents and yielded a grounded theory that explains how parents communicated with their children about smoking. Parents perceived smoking to be a latent danger for their children. To deter smoking from occurring they verbally interacted with their children on the topic and took action by having a no-smoking rule. There were three interaction approaches, which differed by style and method of interaction. Most parents interacted by discussing smoking with their children. They intentionally took advantage of opportunities. Some interacted by telling their children about the health effects of smoking and their opposition to it. They responded on the spur-of-the-moment if their attention was drawn to the issue by external cues. A few interacted by acknowledging to their children the negative effects of smoking. They responded only when their children brought it up. The parents’ intent for the no-smoking rule, which pertained mainly to their homes and vehicles, was to protect their children from second-hand smoke and limit exposure to smoking. The theory can be used by nurses to guide interventions with parents about youth smoking prevention.